Treatment of severe meconium aspiration syndrome with porcine surfactant: A multicentre, randomized, controlled trial (Acta Paediatrica, 2005)
Aim: A randomized, controlled clinical trial was performed in 19 Chinese neonatal intensive care units to evaluate the safety and efficacy of exogenous surfactant replacement therapy for severe meconium aspiration syndrome (MAS) in term and near‐term neonates. Methods: Sixty‐one term infants with severe MAS were randomly assigned to either a surfactant or a control group within 36 h after birth. The infants in the surfactant group (n=31) received an initial dose of porcine lung‐derived surfactant (Curosurf®) at 200 mg/kg, and repeated doses of 200, 100 and 100 mg/kg were given at 6–12 h intervals to a maximum of four doses if oxygenation index (OI) deteriorated by >2 from baseline. The primary outcomes were a reduction of OI to less than 10 and an increase of the pre‐treatment a/A PO2 ratio of 100% over baseline 24 h after surfactant treatment. The secondary outcomes were duration of mechanical ventilation, incidence of complications and survival to discharge from hospital. Results: The general demographic characteristics of the study subjects were similar. There was a trend for surfactant‐treated infants to have an improvement in arterial oxygenation compared to the control group. In comparison with the control group at 24 h, the surfactant group had a lower mean OI (8.1 vs 10.9), more infants with a 100% increase of a/A PO2 (83% vs 48%, p<0.01) over baseline, and a larger area under the curve for PaO2/FiO2 over baseline (3762±1877 vs 2715±1644 mmHg.h, p<0.05). Repeated measures of these parameters were also in favour of the surfactant group during 24 h to 3 and 7 d compared to the baseline (p<0.05). No differences were found in mean duration of mechanical ventilation, incidence of major complications and number of survivors between the two groups. Conclusion: Surfactant replacement therapy improved oxygenation in the study subjects, suggesting that surfactant may have a role in the treatment of severe MAS in term and near‐term infants.